The Invisible University Is COVID-19 Positive. Issue 8 (August 2020) - Park, Daniel S.
Abstract : Within the ivory tower of academia, the coronavirus disease 2019 (COVID-19) pandemic stands to disproportionately impact the invisible workforce of postdoctoral researchers (postdocs). Faced with university closures, hiring freezes, and a general lack of support and benefits, an entire generation of postdocs and their knowledge and skills may be lost to academia without intervention.